2021
DOI: 10.1186/s12884-020-03421-w
|View full text |Cite
|
Sign up to set email alerts
|

Immediate newborn care and breastfeeding: EN-BIRTH multi-country validation study

Abstract: Background Immediate newborn care (INC) practices, notably early initiation of breastfeeding (EIBF), are fundamental for newborn health. However, coverage tracking currently relies on household survey data in many settings. “Every Newborn Birth Indicators Research Tracking in Hospitals” (EN-BIRTH) was an observational study validating selected maternal and newborn health indicators. This paper reports results for EIBF. Methods The EN-BIRTH study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 46 publications
2
32
0
1
Order By: Relevance
“…The qualitative data analysis presented in this paper identified common barriers and enablers for labour ward register recording across all indicators, using health worker and data collector responses together. Indicatorspecific mixed-methods linked analyses will be presented in other linked papers to further explore subthemes and differences between cadres [57][58][59][60][61][62]. It was beyond the scope of this study for the EN-BIRTH data collectors to directly observe or measure the detailed process of register filling (e.g.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The qualitative data analysis presented in this paper identified common barriers and enablers for labour ward register recording across all indicators, using health worker and data collector responses together. Indicatorspecific mixed-methods linked analyses will be presented in other linked papers to further explore subthemes and differences between cadres [57][58][59][60][61][62]. It was beyond the scope of this study for the EN-BIRTH data collectors to directly observe or measure the detailed process of register filling (e.g.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…24 Although women's reporting of EIBF overestimate observed EIBF, self-report still accurately reflects that early breastfeeding is more common among vaginal deliveries than cesarean deliveries. 36 Our study attempted to minimize recall bias to the extent possible by restricting the analysis to the most recent birth in the past 2 years. Our study also assumes the midpoint of the interval reported, which may result in additional bias; however, for the majority of women who reported breastfeeding with 1 hour, shifting coding from 0 hours to 0.5 hours may more accurately reflect the timing of early initiation as babies progress through several initial phases of first relaxing, awakening, and activity before suckling.…”
Section: Limitationsmentioning
confidence: 99%
“…Additionally, survey-based measurement of coverage of care is subject to the ability of respondents to understand the questions and accurately report the answers. Results from validation studies of some newborn care survey questions have shown inconsistent results [52][53][54][55][56][57][58]. In Kenya and Swaziland, for example, interventions such as counselling on breastfeeding and danger signs in the newborn met criteria for accuracy and bias while interventions such examining the baby did not [55].…”
Section: Strengths and Limitationsmentioning
confidence: 99%